Prinsip Kesantunan Berbahasa Dalam Film Layangan Putus Dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia Di SMP - Putri Laras Sati; Petrus Poerwadi; Yuliati Eka Asi; Alifiah Nurachmana; Stefani Ratu Lestariningtyas (Universitas Palangka Raya, 2023)
The research discusses the principle of language politeness in the film Layangan Putus. Therefore, the purpose of this study is to: (1) describe the application of the maxim of wisdom in the dialogue of Layangan Putus film characters, (2) describes the application of the maxim of generosity in the dialogue of Layangan Putus film characters, (3) describes the application of praise maxims in the dialogue of Layangan Putus film characters, (4) describes the application of the maxim of humility in the dialogue of Layangan Putus film characters, (5) describes the application of the maxim of agreement in the dialogue of Layangan Putus film characters, (6) describes the application of sympathy maxims in the dialogue of Layangan Putus film characters, and (7) describe the implications of the research results on the application of the principle of language politeness to Indonesian learning in junior high schools. The method used in this study is a qualitative research method with a descriptive approach and data taken from the dialogue of Layangan Putus film characters. Data collection uses listening methods and note-taking techniques. Data analysis uses data reduction, data feed, and conclusion drawing. The results of research on the application of the principle of language politeness in Layangan Putus film showed that (1) The maxim of wisdom using utterances giving help, advising, refusing help, taking, explaining, replacing the other party, calling, comforting, informing, allowing, serving, hurting the feelings of the other party, and threatening, (2) The maxim of generosity using speech intends to realize the wishes of the other party, delivering, giving food, giving gifts, obeying requests, giving fruits, and sincere, (3) The maxim of praise using utterances of praise, mocking, cursing, and berating, (4) The maxim of humility using speech intends to minimize praise and maximize self-condemnation, admit mistakes, and apologize, (5) The maxim of the agreement using utterances intending to agree, nodding the head, rejecting orders, refusing solicitations, refusing to chat, and refusing requests, (6) The maxim of sympathy using the utterances of condolences and congratulations, (7) The results of this study have implications for Indonesian learning in junior high school grade IX, especially the discussion text material in Basic Competencies 3.10 Examining opinions and arguments that support and that are contra in the discussion text related to the actual problems that are read and heard.